Yu-Gi-Oh! 5D's. Volume 8, Light sense!! - Hikokubo, Masahiro (Viz Media, 2015)
"Yusei and Sect continue their epic duel in Aerial Fortress Seibal. As Sect unleashes a powerful attack, he tells Yusei the Ultimate God is about to return to life. If their friendship is strong enough, they may be able to withstand the Ultimate God's resurrection--but are their struggles all just part of Goodwin's plan?" -- page 4 of cover.